COMPARATIVE ANALYSIS AND THE INFLUENCE OF THE PERCEPTION OF MICRO BUSINESS ACTORS ON THE FINANCING OF SHARIA BANKS AND CONVENTIONAL BANKS: AN EMPIRICAL STUDY IN CIBATU DISTRICT - Rizki Gemilang; Asep Solihin; Eti Jumiati (Journal Tourism Nomic, 2026)
This study aims to analyze the comparison and influence of the perception of micro business actors on the financing offered by Sharia Banks and Conventional Banks in Cibatu District. Using a quantitative approach with a survey design, data was collected through a questionnaire distributed to 74 respondents who are micro business actors who have or are accessing financing services from both types of banks. The results of the study show that the perception of micro business actors towards Sharia Banks is more positive than that of Conventional Banks, especially because the profit-sharing system implemented by Islamic banks is considered fairer and in accordance with religious values. Meanwhile, although Conventional Banks offer easy access, the higher interest burden is an obstacle for some micro business actors. Multigroup Analysis (MGA) revealed that gender did not have a significant effect on financing choices, although men were more likely to choose conventional banks, while women preferred Islamic banks. These findings provide important implications for financial institutions to improve financial literacy and provide a better understanding of the financing products they offer, in order to expand the adoption of formal financing among micro-entrepreneurs. This study also suggests the need to adjust products and financing terms to better suit the needs of micro business actors.